Influence of a Subducted Oceanic Ridge on the Distribution of Shallow VLFEs in the Nankai Trough as Revealed by Moment Tensor Inversion and Cluster Analysis. Issue 15 (7th August 2020) - Toh, A.; Chen, W. J.; Takeuchi, N.; Dreger, D. S.; Chi, W. C.; Ide, S.
Abstract: The eastern Nankai Trough is a unique site where many shallow, very low frequency earthquakes (sVLFEs) are recorded by nearby broadband ocean bottom seismometers. Here, we estimated the locations and seismic moment tensors (MTs) of sVLFEs based on the low‐frequency (<0.07 Hz) components of the records. Although some sVLFEs exhibited long‐duration signals (>100 s), indicating a degree of source complexity, the MT inversions were limited to events with impulsive and short durations (20–30 s). Nevertheless, cluster analysis confirmed that the MTs of impulsive sVLFEs reasonably represented the overall deformation for an event group including many longer‐duration events. The distribution of MTs indicates that deformations associated with sVLFEs are influenced by a subducted oceanic ridge in this region, which produces an along‐the‐trough variation in a strain accumulation/release pattern and probably controls the spatial patterns of tsunami generation. Plain Language Summary: Locations and focal mechanisms of shallow, very low frequency earthquakes in the Nankai Trough were estimated using near‐field and broadband seismic records. The obtained distribution shows that it is influenced by a subducted oceanic ridge in this region. The seismically active area, or the area where strain accumulation/relase take place, appears to be pressed landward by the subducted oceanic ridge. Thus, tsunamigenic slip may occur closer to the landin the region, compared to regions without the subducted ridge. Key Points: Distribution of shallow very low frequency earthquakes in the Nankai Trough was estimated using near‐field broadband seismic records The distribution infers that stress field and strain accumulation/release pattern in this region is influenced by a subducted oceanic ridge The subducted ridge presses seismically active area landward; thus, tsunamigenic slip may occur close to the land compared to other regions